Análisis del índice de morosidad de la cartera de crédito de la Cooperativa de Ahorro y Crédito San Antonio agencia Mata de Cacao periodo 2019-2020 - Mena Muñoz, Briggitte Andrea (2021)
The proposed investigation is developed in the San Antonio savings and credit cooperative in the Mata de Cacao agency of the Febres Cordero parish corresponding to the Babahoyo canton, Los Ríos province and includes an analysis of the delinquency rate of the loan portfolio during the period 2019-2020, since this institution has gained prestige in recent years but is constantly threatened by the non-payment of debts acquired with that institution as a result of microcredits and specific credits that generate problems for the entity such as: poor management in the placement of credits, over-indebtedness of partners, delay and lack of collection management and poor control of payments made, those that are a constant problem for the entity under study since the number of partners that are in default is increasing. The same that through a study and analysis will allow to determine the causes and effects that they have for the company through the use of analytical, descriptive and bibliographic research methods in addition to the use of the line of research corresponding to the career of accounting and auditing management, financial, administrative, tax, auditing and control.